Thermodynamic model and infrared thermography monitoring system for convective drying of goldenberry (Physalis peruviana) - Chuquizuta Trigoso, Tony Steven (2025)
The goldenberry (Physalis peruviana) is a highly perishable Andean fruit with valuable nutritional and functional properties. Its preservation poses a challenge due to its high moisture content. This study presents an integrated method combining infrared thermography (IR) and irreversible thermodynamics to characterize the convective drying process of goldenberry.Samples were dried at 60 ◦C and 1.0 m/s air velocity. Weight loss, surface temperature, and water activity were recorded over 13 h using thermocouples, precision balances, and IR imaging. An irreversible thermodynamic model was applied to estimate water flux, free energy changes, and chemical potential gradients, including mechanical energy effects. The phenomenological coefficient from Onsager’s relation was correlated with water flux to describe internal water migration. IR thermography enabled real-time, non-invasive monitoring of temperature and emissivity, correlating with morphological changes during drying. Sorption isotherms were fitted using the GAB model, and thermodynamic analysis allowed separation of physical and mechanical contributions to water potential. This approach provides a deeper understanding of moisture transport during drying and demonstrates the usefulness of combining IR monitoring with thermodynamic modeling. It offers a promising tool for optimizing drying protocols in high-moisture tropical fruits like goldenberry